Efficacy and Safety of Stem Cell Therapy for T1DM: An Updated Systematic Review and Meta-Analysis - Shi-Yi Sun; Yun Gao; Guan-Jian Liu; Yong-Kun Li; Wei Gao; Xing-Wu Ran (Journal of Diabetes Research)
Background. The long-term insulin therapy for type 1 diabetes mellitus (T1DM) fails to achieve optimal glycemic control and avoid adverse events simultaneously. Stem cells have unique immunomodulatory capacities and have been considered as a promising interventional strategy for T1DM. Stem cell therapy in T1DM has been tried in many studies. However, the results were controversial. We thus performed a meta-analysis to update the efficacy and safety of stem cell therapy in patients with T1DM. Methods. We systematically searched the Medline, EMBASE, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, Web of Science, Wan Fang Data, China National Knowledge Infrastructure, VIP database, and the Chinese Biomedical Literature Database (SinoMed) for relevant studies published before March 19, 2019. The outcomes included parameters for glycemic control (i.e., glycosylated hemoglobin (HbA1c) levels and insulin dosages), β cell function (i.e., fasting C-peptide levels and area-under-curve of C-peptide concentration (AUCC)), and relative risk of adverse events. Statistical analysis was conducted by using RevMan 5.3 and Stata 12.0. Results. Five randomized controlled trials (RCTs) and eight nonrandomized concurrent control trials (NRCCTs) with a total of 396 individuals were finally included into the meta-analysis. Among RCTs, stem cell therapy could significantly reduce HbA1c levels (MD=−1.20, 95% CI -1.91 to -0.49, P=0.0009) and increase fasting C-peptide levels (MD=0.25, 95% CI 0.04 to 0.45, P=0.02) and AUCC (SMD=0.66, 95% CI 0.13 to 1.18, P=0.01). Stem cell therapy could also reduce insulin dosages (SMD=−2.65, 95% CI -4.86 to -0.45, P=0.02) at 6 months after treatment. NRCCTs also had consistent results. Furthermore, RCTs showed stem cell therapy did not increase relative risk of gastrointestinal symptom (RR = 0.69, 95% CI 0.14 to 3.28, P=0.64) and infection (RR = 0.97, 95% CI 0.40 to 2.34, P=0.95). However, NRCCTs showed stem cell therapy increased relative risk of gastrointestinal symptom (RR = 44.49, 95% CI 9.20 to 215.18, P<0.00001). Conclusion. Stem cell therapy for T1DM may improve glycemic control and β cell function without increasing the risk of serious adverse events. Stem cell therapy may also have a short-term (3-6 months) effect on reducing insulin dosages.